2012
DOI: 10.1007/s00223-012-9664-8
|View full text |Cite
|
Sign up to set email alerts
|

High Beta-Palmitate Formula and Bone Strength in Term Infants: A Randomized, Double-Blind, Controlled Trial

Abstract: We aimed to compare the effect of 12-week feeding of commercially available infant formulas with different percentages of palmitic acid at sn-2 (beta-palmitate) on anthropometric measures and bone strength of term infants. It was hypothesized that feeding infants with high beta-palmitate (HBP) formula will enhance their bone speed of sound (SOS). Eighty-three infants appropriate for gestational age participated in the study; of these, 58 were formula-fed and 25 breast-fed infants, serving as a reference group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 32 publications
(29 reference statements)
2
59
0
7
Order By: Relevance
“…In these studies, no effects on infant growth (Kennedy et al, 1999;Nelson and Innis, 1999;Litmanovitz et al, 2013) or on phosphorus and magnesium absorption (Carnielli et al, 1996) were observed. In addition, no cause and effect relationship could be established by the Panel previously between the feeding of formula high in sn-2 palmitate and stool consistency (EFSA NDA Panel, 2014d).…”
Section: Molecular Speciation Of Fatty Acidsmentioning
confidence: 78%
“…In these studies, no effects on infant growth (Kennedy et al, 1999;Nelson and Innis, 1999;Litmanovitz et al, 2013) or on phosphorus and magnesium absorption (Carnielli et al, 1996) were observed. In addition, no cause and effect relationship could be established by the Panel previously between the feeding of formula high in sn-2 palmitate and stool consistency (EFSA NDA Panel, 2014d).…”
Section: Molecular Speciation Of Fatty Acidsmentioning
confidence: 78%
“…Outcomes associated with feeding of infant formulas may be improved by the addition of components with specific functions, such as structured lipids rich in sn -2 palmitic acid (4,5,7,3032) and also nondigestible oligosaccharides (8–11). These types of ingredients have been evaluated independently in previous studies; however, the effects of their combination have received only limited attention (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…For 27 RCT publications the risk of bias was evaluated as high (Bayley et al 2002;Birch et al 2010;Colombo et al 2011;Cordle et al 2002;Daniels et al 2008;Davis et al 2008;de Jong et al 2011;de Jong et al 2012;Demmers et al 2008;Drover et al 2012;Fewtrell et al 2013;Field et al 2010;Field et al 2008a;Field et al 2008b;Forsyth et al 2003;Gibson et al 2005;Heubi et al 2000;Koo et al 2003;Lasekan et al 2006;Lasekan et al 2011;Lien et al 2004;Raes et al 2010;Roze et al 2012;Schaller et al 2004;Trabulsi et al 2011;Tuthill et al 2002;Willats et al 2013) and for 3 RCT's the risk of bias was evaluated as moderate (Borschel et al 2012, Litmanovitz et al 2013, Singhal et al 2010). None of the RCT's was evaluated as having a low risk of bias, since all RCT's had been funded, at least partially, by a profit organization.…”
Section: Health-related Outcome Study Type Proteinmentioning
confidence: 99%
“…For the cohort studies, including RTC's which compare FM and BM, we evaluated the risk of bias as high in 18 publications (Aliet et al 2007;Bayley et al 2002;Birch et al 2007;Bulk-Bunschoten et al 2002;Davis et al 2008;Demmers et al 2005;Dube et al 2010;Field et al 2010, Field et al 2008a, Field et al 2008bGong et al 2008;Litmanovitz et al 2013;Makrides et al 2000a;Raes et al 2010;Regnault et al 2010;Sarafidis et al 2007;Savino et al 2013;Trabulsi et al 2011) and as moderate in 5 studies (Baird et al 2008;Butte et al 2000;Duijts et al 2010;Evelein et al 2011;Hetzner et al 2009). Detailed quality assessment tables are presented per study in Appendix IV for the reviews and in V for the individual publications.…”
Section: Health-related Outcome Study Type Proteinmentioning
confidence: 99%